Exploring Psychological Realism in Bijay Malla’s “Sunglasses” and “The Prisoner and the Dove” - Budhathoki, Mahendra Kumar (Bon Voyage, 2024)
This article explores psychological realism in Bijay Malla’s two stories: “The Prisoner and the Dove” and “Sunglasses.” The study addresses how the characters construct certain thoughts, emotions, and feelings in their minds after observing and experiencing real-world events and conditions. It analyzes the psyches, thoughts, and psychological intricacies of individuals in lifelike situations in Malla’s stories from the viewpoint of psychological realism. The methodology involves a detailed analysis of Malla’s narrative techniques and character portrayals, using the theoretical framework of psychological realism to interpret the mental and emotional states of the characters. By examining the intricacies of the characters’ inner lives and their responses to their environments, the study aims to uncover the psychological depth in the stories. It reveals that Malla effectively presents photographic images of characters’ minds and psyches in both stories. In “Sunglasses,” Malla portrays the contradictory mental state of the narrator after observing his wife’s relationship with another man. In “The Prisoner and the Dove,” Malla presents the psyches and mindsets of political prisoners in jail. These two stories depict the protagonists’ contradictions and complex psyches within contemporary socio-cultural and political environments.